2021
DOI: 10.3390/ijms22179369
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Derived Xenograft Models in Cervical Cancer: A Systematic Review

Abstract: Background: Patient-derived xenograft (PDX) models have been a focus of attention because they closely resemble the tumor features of patients and retain the molecular and histological features of diseases. They are promising tools for translational research. In the current systematic review, we identify publications on PDX models of cervical cancer (CC-PDX) with descriptions of main methodological characteristics and outcomes to identify the most suitable method for CC-PDX. Methods: We searched on PubMed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 94 publications
(199 reference statements)
0
23
0
Order By: Relevance
“…Previously, we reported that 61 CC-PDXs were established from tumor tissues obtained from 98 patients with cervical cancer; the overall enrollment rate was 62.2% [ 23 , 24 , 25 , 26 , 27 ]. A tumor fragment of 1–3 mm 3 may be suitable for establishing CC-PDX [ 28 ]. Hoffman et al reported the implantation of 3–5 mm tumor fragments into SCID mice; however, no viable tumors were observed [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we reported that 61 CC-PDXs were established from tumor tissues obtained from 98 patients with cervical cancer; the overall enrollment rate was 62.2% [ 23 , 24 , 25 , 26 , 27 ]. A tumor fragment of 1–3 mm 3 may be suitable for establishing CC-PDX [ 28 ]. Hoffman et al reported the implantation of 3–5 mm tumor fragments into SCID mice; however, no viable tumors were observed [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, no association was observed between engraftment rate and clinical characteristics of the patients; however, all adenocarcinomas failed to grow. In general, tumor fragments obtained from patients with a large tumor size or advanced stage have a higher success rate of transplantation than tumors obtained from patients with less-advanced disease [ 28 ]. Most established CC-PDX is squamous cell carcinoma [ 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient-derived xenograft (PDX) models is another valuable animal model which closely resemble the tumor features of patients and retain the molecular and histological features of diseases. A recent systematic review of PDX of cervical cancer revealed among 98 donor patients, 61 CC-PDX were established, and the overall success rate was 62.2% (0% to 75%) [ 142 ]. No correlation was found between the engraftment rate and characteristics of the tumor and donor patient, including histology, staging, and metastasis.…”
Section: Animal Models Of Cervical Cancer and Their Usesmentioning
confidence: 99%
“…Furthermore, this Special Issue included a review [ 8 ] with regards to cervical cancer pathogenesis and its potential diagnostic biomarkers and a systematic review [ 9 ] of 10 original studies with respect to the optimal patient-derived xenograft (PDX) models of cervical cancer. We would care to express our sincere gratitude to all the contributors to this Special Issue of Gynecologic Oncology for IJMC, providing their expert contributions, either as experimental or reviewed data, which will assuredly attract the scientific audience’s attention and undoubtedly encourage the publication of further, high-quality, research papers in the second edition of the Special Issue entitled: “Advances in Gynecological Cancers 2.0”.…”
mentioning
confidence: 99%